Reliability and validity of field-based tests to assess upper-body muscular strength in children aged 6-12 years - Fernandez Santos, J. R.; Ruiz, J. R.; Gonzalez-Montesinos, J. L.; Castro-Piñero, J. (Pediatric Exercise Science, 2016)
The aim of this study was to analyze the reliability and the validity of the handgrip, basketball throw and pushups tests in children aged 6-12 years. One hundred and eighty healthy children (82 girls) agreed to participate in this study. All the upper body muscular fitness tests were performed twice (7 days apart) whereas the 1 repetition maximum (1RM) bench press test was performed 2 days after the first session of testing. All the tests showed a high reproducibility (ICC > 0.9) except the push-ups test (intertrial difference = 0.77 ± 2.38, p < .001 and the percentage error = 9%). The handgrip test showed the highest association with 1RM bench press test (r = .79, p < .01; R2 = .621). In conclusion the handgrip and basketball throw tests are shown as reliable and valid tests to assess upper body muscular strength in children. More studies are needed to assess the validity and the reliability of the upper body muscular endurance tests in children.